Challenges in Banking: A Nepalese Diaspora - Panta, Radhesh (Socio-Economic Development Panorama, 2008)
Nepal has become member of World Trade Organization (WTO) and has committed to open Financial Services Sector (FSS) especially banking services to the foreign banks and financial institutions by 2010. This could be threat as well as opportunities for banking sector of Nepal. The existing level of Non-Performing Assets (NPA) is not that much healthy sign for the smooth growth of banking sector. One should seriously need to re-think proper strategy for managing NPA. The predominance of rural economy urge bank and financial institutions of Nepal to peneterate in this sector with innovative products of microfinance as insurence, remittance, etc.so as to support poverty alleviation programme. Expansion of Small and Medium Sized Enterprises (SMEs) in rural sector could lured to banking sector to invest on it too. Managing inflow of remittances would yield fruitful outcome for Nepal. Public private partnership concept will be equally desirable for poverty alleviation, growth and expansion of banking service especially in the rural economy. Socio-Economic Development Panorama Vol. 1. No. 2 (2007) pp. 9-22